Designing A Combustion Chamber For Cascading Thermoelectric And Thermophotovoltaic Power System - Muhaimi, Nur Muhaimin Aidil (Universiti Sains Malaysia, 2017)
This work focuses on the design of the combustion chamber which is used for cascading the thermoelectric (TE) and thermophotovoltaic (TPV) power system. Thus, the design is according to the characteristics of each of the cells itself where the suitable position of installation on both cells in the combustion chamber is needed. One of the important characteristic is due to how the cells is functioning to generate the electricity so, for TPV cell is converting the radiation energy into the electricity and TE cell convert the thermal energy directly into the electricity. However, TE cells have low efficiency for generate electric power than TPV cells. The development of concept of the design in cascading TE and TPV power generation is where the used heat stream or produced by the TPV is applied to the input of TE cells. The picture of the design as the combustion chamber in a vertical cylinder shape, the TE and TPV cells is installed in vertical sequence where the TE is on the top of the chamber and TPV cells at the middle of the chamber which is closer to the source. Besides, the combustion chamber use the porous media combustion (PMC) as the source of combustion to enhance the combustion process. Furthermore, one of the important characteristic of this design is the swirl flow of air in the combustion chamber. The tangential tunnel to the combustion chamber was designed to make the swirl flow. It is an enormous challenge to fabricate this part due to the curvy surface but it can enhance the heat transfer in the combustion chamber. In other hand, TE plate is designed to be an adjustable height with five difference height to have a good position for the TE modules. Based on the experiment, temperatures reading show the design is acceptable.